The Effect of Good Corporate Governance, Green Accounting and Gender Diversity on the Financial Performance of Manufacturing Companies in BEI - Wandasari, Dila; Nasution, Yenni Samri Juliati; Syafina, Laylan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to examine the effect of Good Corporate Governance, Green Accounting and Gender Diversity on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022, both partially and simultaneously. This study uses a quantitative approach with purposive sampling, obtaining 50 observation data from 10 companies. The types and sources of data used in this study are secondary data in the form of financial statements or annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. Multiple linear regression analysis was conducted in this study with the help of SPSS 23 software. According to the research findings, Good Corporate Governance and Green Accounting have a significant positive effect on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. However, from 2018 to 2022, Gender Diversity has no effect on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study has limitations, namely the difficulty of accessing data on each company's website because there are several companies with incomplete data.